Level of Blood Pressure Control Among Hypertensive Patients at Cardiology OPD of PMCH Nawabshah - Qurban Ali Rahu, Imran Ellahi Soomro, Shabaz Ali Shaikh, Faiz Memon, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objectives: To analyze the percentage of hypertensive patients having their blood pressure (BP) controlled at Cardiac OPD of PMCH Nawabshah. Study Design: Descriptive, cross sectional study. Place & Duration: Cardiac OPD of PMCH, Nawabshah, from May 2014 to July 2014. Material and Methods: 224 hypertensive cases having antihypertensive therapy were included for the study. The blood pressure of all the patients was measured according to AHA guidelines on blood pressure measurement. All the related data was collected on a predesigned proforma, and the results were statistically analyzed and tabulated. Results: Out of 224patients, 104 were male. BP was controlled in only 28 (12.5%) out of 224 patients. Blood pressure of female was better controlled than male counterparts (20% vs 5%). Patients with relatively younger age (between 25-45 years) were having better control (20% vs. 8.3%) as compared to those who were relatively elder (>45 years). Conclusion: We conclude that situation is very worse regarding this major health problem. These are the patients who are already diagnosed to have hypertension and are concerned about their disease and despite coming in OPD and seek advice for their health problem, still these patients have their BP poorly controlled.